Factors Affecting Quality of Life in Hypertensive Patients: A Cross-Sectional Study in Hue, Vietnam - Dang Thi Han Ny; Le Van An; La Thanh Hai; Pham Van Quan (Nurse Media: Journal of Nursing)
Background: Hypertension is a common chronic condition that leads to serious complications and negatively affects patients’ quality of life (QoL). Therefore, improving hypertension management and understanding factors that influence QoL has become an important goal in patient care. However, in Hue, Vietnam, no research has been conducted to evaluate how sociodemographic factors affect the QoL of hypertensive patients.